Veterinary clinicians as One Health messengers: opportunities for preventing zoonoses while promoting biophilia in the United States - Overcast, Macon (Frontiers in Conservation Science, 2025)
One Health is a transdisciplinary approach to health science that recognizes the linked and interdependent ecology of environmental, human, and animal health. Effective communication of zoonotic disease risks through a One Health framework presents an opportunity to both prevent emerging infectious diseases and enhance public appreciation for wildlife and conservation, herein termed biophilia. While veterinary practitioners have historically played a pivotal role in public health and conservation, structural changes in the veterinary profession—including the dominance of companion animal practice, fee-for-service models, and corporate consolidation—limit their potential as One Health communicators, and thus wildlife conservation advocates. Additionally, the human-animal bond is often singularly framed as a health resource for pet owners and companion animals, neglecting its broader role within communities and its connection to other social, ecological, and epidemiological networks that include human and wildlife populations. This article outlines key constraints facing veterinarians as One Health communicators and proposes two solutions to integrate preventive zoonoses messaging and biophilia promotion within veterinary clinical practice: (1) the human-animal bond should be reconceptualized within veterinary clinical sciences as a community-level resource akin to natural capital, and (2) the veterinary extension workforce should be expanded to include agents facilitating local conservation and public health information exchange with companion animal veterinarians. Through these solutions, he veterinary profession can further enhance its principal role in One Health. Such efforts would empower veterinarians to communicate about zoonotic disease risks and conservation, ensuring that One Health principles are embedded in everyday clinical interactions and broader community initiatives.